2019
DOI: 10.1371/journal.pone.0211810
|View full text |Cite
|
Sign up to set email alerts
|

Optical tweezers as an effective tool for spermatozoa isolation from mixed forensic samples

Abstract: A single focus optical tweezer is formed when a laser beam is launched through a high numerical aperture immersion objective. This objective focuses the beam down to a diffraction-limited spot, which creates an optical trap where cells suspended in aqueous solutions can be held fixed. Spermatozoa, an often probative cell type in forensic investigations, can be captured inside this optical trap and dragged one by one across millimeter-length distances in order to create a cluster of cells which can be subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…Optical trapping has previously been used to study sperm motility under various conditions (Nascimento, Botvinick, Shi, Durrant, & Berns, 2006; Tadir et al, 1989) and also applied to cell sorting on a microfluidic chip (Wang et al, 2011). This application was recently extended to selective isolation of sperm (Auka et al, 2019). The optical tweezer is a high‐density focused laser beam that uses an immersion objective lens on an inverted microscope to form an optical trap, capable of holding dielectric particles in the center (Ashkin, Dziedzic, Bjorkholm, & Chu, 1986).…”
Section: Isolation Of Male Dna In Sexual Assault Cases—alternatives Amentioning
confidence: 99%
See 1 more Smart Citation
“…Optical trapping has previously been used to study sperm motility under various conditions (Nascimento, Botvinick, Shi, Durrant, & Berns, 2006; Tadir et al, 1989) and also applied to cell sorting on a microfluidic chip (Wang et al, 2011). This application was recently extended to selective isolation of sperm (Auka et al, 2019). The optical tweezer is a high‐density focused laser beam that uses an immersion objective lens on an inverted microscope to form an optical trap, capable of holding dielectric particles in the center (Ashkin, Dziedzic, Bjorkholm, & Chu, 1986).…”
Section: Isolation Of Male Dna In Sexual Assault Cases—alternatives Amentioning
confidence: 99%
“…The optical tweezer is a high‐density focused laser beam that uses an immersion objective lens on an inverted microscope to form an optical trap, capable of holding dielectric particles in the center (Ashkin, Dziedzic, Bjorkholm, & Chu, 1986). For the separation of sperm, a sperm is held in an optical trap, prior to transfer into a capillary for collection (Auka et al, 2019). Similar to LMD, 50 sperm are required to generate a high‐quality DNA profile.…”
Section: Isolation Of Male Dna In Sexual Assault Cases—alternatives Amentioning
confidence: 99%
“…Mixture deconvolution is one of the most engaging topics in forensics. Over previous years different methods have been developed to assist the process, both prior to [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] and after, DNA typing of a mixed trace [ 36 , 37 , 38 ]. The DEPArray System, which uses a dielectrophoresis grid to isolate single cells, is a promising cell separation technology for forensic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The main motivation behind introducing this technology into forensics is the potential to improve mixture deconvolution workflows and interpretation methods. If a trace is a mixture of different biological materials (for example, sperm and epithelium), there are methods to separate cell pools to investigate them separately [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Problems arise when the mixed trace is too complex or if it consists of the same cell type, such as blood-blood mixtures [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three studies continue to look at novel means of separating sperm cells from other cells to assist the interpretation of DNA profiles generated downstream. These include the application of optical tweezers [107], acoustic differential extraction technologies [108], and capillary zone electrophoresis [109]. Furthermore, using DEPArray™ technology (Menarini Silicon Biosystems, Bologna, Italy), Anslinger et al [110] demonstrated the ability to obtain complete DNA profiles from isolated single white cells from each of the two or three known contributors to mixed stains.…”
Section: Preferential Recovery From Mixed Samplesmentioning
confidence: 99%